Study on Productivity Improvement of Hill Goat Through Selective Breeding Programme - Pokharel, P. K.; Neopane, S. P. (Nepal Journal of Science and Technology, 2007)
An Attempt for the first time ever in the livestock species has been made to the production potentiality of hill goat through selective breeding. Two tier open nucleus breeding had been assiduously applied in order to enhance the genetic gain off hill goats. Breeding records of 221 does and 1462 kids in nucleus herd, and records of 968 does and 1622 kids in on-farm condition fathered selected bucks during 1998 to 2004 were considered for the study. Selection response of the breeding programme was calculated in terms of genetic gain. Response of selection for the first generation kids in nucleus flock at station was found to be 2.77 and 9.6 per cent generation for four and six month weights respectively. Similarly, overall twinning ability of hill goats for the period was increased by 0.73 per cent reaching the level of 68.75. In on-farm condition response of selection for first generation kids per year were 0.22, 7.01 and 7.41 percent for birth, four and six month weight respectively. Likewise, twinning frequency was improved by 27 percent indicating the level of 55. In both low and mid altitudes (up to 1100 masl) of eastern hill the selection program was found effective for improving the overall productivity of local hill goats, and could be equally effective for other parts of the country. Nepal Journal of Science and Technology Vol. 7, 2006 pp. 1-7